2012
DOI: 10.1038/nrd3846
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial proteolytic complexes as therapeutic targets

Abstract: Proteases have been successfully targeted for the treatment of several diseases, including hypertension, type 2 diabetes, multiple myeloma, HIV and hepatitis C virus infections. Given the demonstrated pharmacological tractability of this enzyme family and the pressing need for novel drugs to combat antibiotic resistance, proteases have also attracted interest as antibacterial targets--particularly the widely conserved intracellular bacterial degradative proteases, which are often indispensable for normal bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 103 publications
2
118
0
Order By: Relevance
“…It has been suggested that Clp proteolysis is essential for the survival of Mtb, though this system is currently understudied. Furthermore, the Clp proteolysis complex is increasingly being recognized as a key druggable target (38), especially in Gram-positive bacteria (39,40), including Mtb (41-43). There are key implications of Rv2745c and the ATP-dependent Clp proteolysis genes being induced during stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Clp proteolysis is essential for the survival of Mtb, though this system is currently understudied. Furthermore, the Clp proteolysis complex is increasingly being recognized as a key druggable target (38), especially in Gram-positive bacteria (39,40), including Mtb (41-43). There are key implications of Rv2745c and the ATP-dependent Clp proteolysis genes being induced during stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cymA exhibits hepatic clearance and a short half-life in mice, and ecumicin has limited solubility and poor intestinal absorption. 13,73 Recent total syntheses and fermentation optimization may aid in these developments. [76][77][78] Although drugs targeting ClpC1 are an intriguing possibility for anti-M. tuberculosis therapeutics, they generally do not have bactericidal activity against species other than actinobacteria.…”
Section: Aaa+ Atpase Uncouplers As Therapeuticsmentioning
confidence: 99%
“…In contrast, intracellular proteases are multimeric complexes with little substrate specificity but whose activity and substrate selection are tightly regulated. 13 To achieve this level of regulation, catalytic sites are hidden in barrel-like structures and gaining access requires substrate selection and unfolding. In this way, the protease is able to specifically target a wide range of substrates, including not only Figure 1 Protease catalytic mechanisms.…”
Section: Proteases As Drug Targetsmentioning
confidence: 99%
See 2 more Smart Citations